Spectral densities and diagrams of states of one-dimensional ionic Pauli conductor - Stasyuk, I.V.; Vorobyov, O.; Stetsiv, R.Ya. (Condensed Matter Physics, 2011)
We focus on the features of spectra and diagrams of states obtained via exact diagonalization technique for finite ionic conductor chain in periodic boundary conditions. One dimensional ionic conductor is described with the lattice model where ions are treated within the framework of "mixed" Pauli statistics. The ion transfer and nearest-neighbour interaction between ions are taken into account. The spectral densities and diagrams of states for various temperatures and values of interaction are obtained. The conditions of transition from uniform (Mott insulator) to the modulated (charge density wave state) through the superfluid-like state (similar to the state with the Bose-Einstein condensation observed in hard-core boson models) are analyzed.